2010
DOI: 10.1346/ccmn.2010.0580304
|View full text |Cite
|
Sign up to set email alerts
|

Use of Natural and Modified Magadiite As Adsorbents to Remove Th(IV), U(VI), and Eu(III) from Aqueous Media — Thermodynamic and Equilibrium Study

Abstract: The contamination of aquatic environments by toxic metals such as radionuclides is of great concern because of the tendency of those metals to accumulate in the vital organs of humans and animals, causing severe health problems. The objective of this study was to investigate the use of natural and modified magadiite clay as an adsorbent to remove Th(IV), U(VI), and Eu(III) from aqueous solutions. Magadiite from the Amazon region, Brazil, was modified chemically with 5-mercapto-1-methyltetrazole (MTTZ) using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Layered silicates such as magadiite (NaSi 7 O 13 (OH) 3 . 4H 2 O), kenyaite (Na 2 Si 22 O 41 (OH) 8 .6H 2 O) and kanemite (NaHSi 2 O 5 .3H 2 O) have recently become the subject of great interest due to their adsorptive and catalytic properties (Alarcón et al, 2005; Kalvachev et al, 2006; Park et al, 2009; Royer et al, 2010; Guerra et al, 2012; Kim et al , 2012; Chen et al, 2016). The structure of kenyaite is composed of silica layers and interlayer hydrated cations; each silica layer is built from three silica sheets instead of two, as in the case of magadiite (Wang et al, 2006).…”
mentioning
confidence: 99%
“…Layered silicates such as magadiite (NaSi 7 O 13 (OH) 3 . 4H 2 O), kenyaite (Na 2 Si 22 O 41 (OH) 8 .6H 2 O) and kanemite (NaHSi 2 O 5 .3H 2 O) have recently become the subject of great interest due to their adsorptive and catalytic properties (Alarcón et al, 2005; Kalvachev et al, 2006; Park et al, 2009; Royer et al, 2010; Guerra et al, 2012; Kim et al , 2012; Chen et al, 2016). The structure of kenyaite is composed of silica layers and interlayer hydrated cations; each silica layer is built from three silica sheets instead of two, as in the case of magadiite (Wang et al, 2006).…”
mentioning
confidence: 99%
“…On the other hand, different silica sources were used to prepare Na-magadiite, and there was not a systematic reason as to why one source was favored over the others. For example, by using silica gel as a source of silica, a pure magadiite phase was obtained at 150 • C for 3 days [14]; however, the same phase required 8 days of reaction at 150 • C using colloidal silica (40% in water) [15]. The reaction time was reduced to 3 days using Ludox-HS40 [16].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, several researchers introduce different organic ligands into the solid matrix to increase their extraction capacities [7 10]. Guerra et al [11] reported the use of natural and modified magadiite as adsorbents to remove Th(IV), U(VI), and Eu(III) from aqueous media in thermodynamic and equilibrium study. In most cases, the amount of heavy metal absorbed onto these organo-modified clays was much greater than that adsorbed onto the unmodified clays under the same experimental conditions [12,13].…”
Section: Introductionmentioning
confidence: 99%